Temporal patterns control carbon balance in forest and agricultural tropical peatlands in North Selangor, Malaysia - Vijayanathan, Jeyanny; Ishak, Mohammad Fakhri; Parlan, Ismail; Omar, Hamdan; Haruna, Ahmed Osumanu; Lion, Marryanna; Hassan, Mohd Ghazali; Jong, Regina Mariah; Abu Samah, Abdul Khalim (Societa Italiana di Selvicoltura ed Ecologia Forestale (S I S E F), 2021)
Tropical peat swamp forests can sequester significant amount of carbon (C). However, there is dearth of understanding on the tropical soils’ C stocks and emissions because of the changes in peatland use, land use policies, and micro-climate. The objective of this study was to determine the C stocks and fluxes of two peat swamp forests and a peatland under mixed cropping in Selangor, Malaysia. Standard procedures were used to determine aboveground biomass, belowground biomass, selected peat soil physical, chemical, and biological properties, and environmental variables that are related to peat soil respirations. The mean C stocks for the peat swamp forest and mixed cropping sites were 1788.79 Mg C ha-1 and 1023.57 Mg C ha-1, respectively. The carbon dioxide emission rates of peat swamp forest and mixed cropping sites ranged from 7.20 to 73.13 tCO2 ha-1 year-1 and 26.50 to 43.43 tCO2 ha-1 year-1, respectively. These emissions are related to seasonal changes because the relative humidity, soil temperature, and ground water of the experimental sites had significant effects on soil respiration. Unlike the mixed cropping sites, the fluxes of the peat swamp forest were significantly higher in the dry season compared with the wet season. These findings suggest that peat soil respiration is controlled by relative humidity, temperature, and the changes in ground water table. Continued monitoring and conservation efforts to preserve stored C in peatlands are essential.